Becoming the Mentors We Needed: Formative First-Year Practices and Motivating Factors of Peer Mentorship in College - Todd, Sarah (Christian higher education, 2023)
The purpose of this qualitative study was to examine formative first-year practices and motivating factors that encouraged first-year college students to pursue peer mentorship roles. The examination of peer mentorship within undergraduate populations owes much to Jacobi’s (1991) study on mentoring and academic success, which more recently has been continued by Nora and Crisp (2007), Crisp and Cruz (2009), and Crisp et al. (2017). Peer mentorship bolsters both individual student development and undergraduate enrollment (Crisp et al., 2017; Yomtov et al., 2017), and assuming a peer mentor role contributes in meaningful ways to a college learning environment (Kuh et al., 2011). Although a significant amount of research has been conducted on peer mentorship, there has been less focus on motivating factors during the first year of college that prompt peer mentors to seek such roles in their second year of undergraduate education. The results of this study indicated students were motivated to pursue peer mentorship roles for four reasons: the desire for community, their sense of self-efficacy, a vocational connection, and the opportunity to impact incoming students’ experiences. Implications of these results are discussed in terms of implementing formative best practices into first-year experiences as a means of encouraging and recruiting second-year peer mentors.